Perlindungan Hukum Bagi Para Pihak Dalam Perjanjian Pinjam Meminjam Uang (Study Dalam Perjanjian Non Kontraktual Dengan Jaminan Fidusia) - Ningsih, Sri Widia, Septarina Budiwati, SH.,MH, Shalman Al-Farizi, SH.,M.Kn (2016)
This study aims to determine the binding force of a treaty borrowing money which is done with the non-contractual fiduciary guarantee and to determine the legal protection for the parties involved in the agreement are lending money to the non-contractual fiduciary in Desa Perintis, Kec. VII Koto Ilir, Kab. Tebo, Jambi. The method used is empirical juridical with descriptive research. The data source consists of primary data, interviews and secondary data is data of primary and secondary law. Data were collected by literature study and interviews and then analyzed qualitatively. The results showed borrowing agreements by way of verbal (non-contractual) allowed under the legislation, as set out in Article 1338 of the Civil Code 1320 jo. Legal protection against the parties to the agreement to borrow to borrow money verbal (non-contractual) carried by several ratings are an assessment of the character, an assessment of the ability to manage the business to be run, an assessment of the capital, an assessment of the collateral, without the use of collateral in particular either in the form of chattels or immovable then it can only rely on the guarantee of a general nature as described in Article 1131 and 1132 of the Civil Code, where one party is in default were solved amicably negotiations.